IMPLEMENTASI PRINSIP KEPEMIMPINAN RASUL PAULUS BERDASARKAN SURAT 1 TIMOTIUS 3:1-13 & 2 TIMOTIUS 2:2-6 DI KALANGAN CIVITAS AKADEMIKA SEKOLAH TINGGI TEOLOGI - Tenny Tenny; Areyne Christi (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract: Theory basis: Christian leadership which is more spiritual in nature as a person's ability to influence others comes from the Holy Spirit. Research objective: is to answer the following questions, (1) What is the level of implementation of the leadership principles of the Apostle Paul based on letters 1 Timothy 3: 1-13 and 2 Timothy 2: 2-7 among the STT Duta Panisal Academic Community? (2) Which dimension predominantly determines the implementation of Paul's leadership principles based on letters 1 Timothy 3: 1-13 and 2 Timothy 2: 2-7 among the STT Duta Panisal Academic Community? (3) Which category of background determines the implementation of the leadership principles of the Apostle Paul based on 1 Timothy 3: 1-13 and 2 Timothy 2: 2-7? Method: The explanatory-confirmatory method. Moderate Variable or Moderate Variable is the comparison variable, namely gender, age, status, education, ethnicity, church of origin, and occupation. The results of the study: (1) the hypothesis of the level of implementation of the leadership principles of the Apostle Paul based on Letter 1 Timothy 3: 1-13; & 2 Timothy 2: 2-6 among the academic community of Duta Panisal Theology College are in the high category. (2) The Principles of the Apostle Paul's Leadership Based on 1 Timothy 3: 1-13; & 2 Timothy 2: 2-6 is significantly at α <0.05, the acquisition score is 875,889. (3) Ethnic background is the most dominant background category shaping the Implementation of Leadership Principles among the Academic Community of Duta Panisal Theological College. Abstrak: Landasan Teori: Kepemimpinan Kristen yang lebih bersifat rohani sebagai kemampuan seseorang untuk mempengaruhi orang lain datangnya dari Roh Kudus. Tujuan Penelitian: adalah menjawab pertanyaan-pertanyaan sebagai berikut, (1)Berapakah besar tingkat implementasi prinsip-prinsip kepemimpinan Rasul Paulus berdasarkan surat 1 Timotius 3:1-13 dan 2 Timotius 2:2-7 di kalangan Civitas Akademika STT Duta Panisal? (2)Dimensi manakah yang paling dominan menentukan implementasi prinsip kepemimpinan Paulus berdasarkan surat 1 Timotius 3:1-13 dan 2 Timotius 2:2-7 di kalangan Civitas Akademika STT Duta Panisal? (3)Kategori latar belakang manakah yang lebih menentukan implementasi prinsip-pinsip kepemimpinan Rasul Paulus berdasarkan surat 1 Timotius 3:1-13 dan 2 Timotius 2:2-7? Metode: metode Eksplanatori-Konfirmatori. Variabel Moderat atau Moderate Variable adalah variabel pembanding yaitu jenis kelamin, umur, status, pendidikan, suku, gereja asal, dan pekerjaan. Hasil penelitian: (1) hipotesa Tingkat Implementasi prinsip kepemimpinan Rasul Paulus berdasarkan Surat 1 Timotius 3:1-13; & 2 Timotius 2:2-6 di kalangan civitas akademika Sekolah Tinggi Teologi Duta Panisal berada dalam kategori tinggi. (2) Prinsip Kepemimpinan Rasul Paulus Berdasarkan Surat 1 Timotius 3:1-13; & 2 Timotius 2:2-6 secara signifikan ada pada α <0,05 , perolehan skor sebesar 875.889. (3) latar belakang Suku menjadi kategori latar belakang paling dominan membentuk Implementasi Prinsip Kepemimpinan di Kalangan Civitas Akademika Sekolah Tinggi Teologi Duta Panisal.